Medicinal Plants of Central Asia: Uzbekistan and Kyrgyzstan - Eisenman, Sasha W.; Zaurov, David E.; Struwe, Lena (Springer New York : Imprint: Springer, 2013)
Medicinal Plants of Central Asia: Uzbekistan and Kyrgyzstan is the first English-language book detailing medicinal plant diversity in the region. More than two hundred of the most important medicinal plants of Central Asia are listed and it includes many whose medicinal uses and activities are being compiled for the first time.  Information on the taxonomy, morphology, ecology, ethnobotany, chemistry, and pharmacology of plants from this region are presented with hundreds of beautiful color photographs. The book is co-authored by scientists from Kyrgyzstan, Uzbekistan and the U.S. and draws upon a rich source of local knowledge. The extensive English-Russian linguistic glossary to ecological, botanical, chemical, and medical terms is the first of its kind for this type of book.  Dr. Sasha Eisenman received his Ph.D. from Rutgers University. He is currently Assistant Professor in the Department of Landscape Architecture and Horticulture at Temple University. His research focuses on chemical and genetic variation in medicinal plants, conservation genetics of rare species, and investigating underutilized plant species. Dr. David Zaurov received his Ph.D. from the Tashkent Agricultural Institute, USSR and since 1992 he has worked in various capacities at Rutgers University, including as a faculty member in the Plant Biology Department. He is the author of nearly 100 research articles and 3 textbooks. In 1998, he was acknowledged as an Honorary Professor of Tashkent State Agrarian University, the Republic of Uzbekistan. Dr. Lena Struwe is an Associate Professor and Director of the Chrysler Herbarium at Rutgers University, New Jersey, USA, and has over 25 years of research and teaching experience in the fields of botany and medicinal plants.  Her expertise is in the evolution and taxonomy of gentians, anti-malarial plants, and the ways in which humans have used plants throughout history.